Training and Mentoring on Strengthening Literacy and Numeracy in Red Reporting School Learning Recovery - Wahyu Indra Bayu; Herri Yusfi; Fitri Agung Nanda; Silvi Aryanti; Ahmad Richard Victorian; Syarifuddin Syarifuddin; Samsul Azhar; Ilham Agustian Saputra; Anggar Setia Budi (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
A training and mentoring programmed to strengthen literacy and numeracy in schools with red report cards was implemented as a post-pandemic learning recovery effort. The programmed aims to improve the literacy and numeracy skills of students who are still below national standards, especially in schools with low learning outcomes. Through intensive training, teachers are empowered with pedagogical knowledge and skills to implement effective learning methods that suit learners' needs. This research method uses a qualitative-descriptive approach, collecting data through observation, interviews, and documentation studies. The results showed that the training and mentoring programmed succeeded in improving teachers’ competence in teaching and increasing students’ learning motivation. Thus, this programmed is expected to have a positive impact on strengthening teachers' capacity in implementing effective and sustainable learning. The findings provide important recommendations for the government and stakeholders in developing education policies that focus on restoring learning, particularly in low-performing schools.